1993
DOI: 10.1017/s0043174500076037
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Period of Weed Control in White Bean (Phaseolus vulgaris)

Abstract: Field studies were conducted in 1986 and 1987 to determine the critical period for weed control in white bean grown in Ontario. The treatments consisted of either allowing weeds to infest the crop for increasing durations after planting or maintaining plots weed free for increasing durations after planting. The beginning of the critical period was defined as the crop stage by which weed interference reduced yields by 3%. Similarly, the end of the critical period was defined as the crop stage to which the crop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 21 publications
(33 reference statements)
2
47
0
2
Order By: Relevance
“…Given that weed infestations early in the growing season may create conditions resulting in crop yield losses, early-season weed population dynamics should not be ignored. The critical period of weed control in white bean starts at the appearance of the second trifoliate and lasts from 3 to 5 wk thereafter (Woolley et al 1993). The results presented here suggest that weed management in snap bean should not be delayed until the appearance of the second trifoliate.…”
Section: Resultsmentioning
confidence: 71%
“…Given that weed infestations early in the growing season may create conditions resulting in crop yield losses, early-season weed population dynamics should not be ignored. The critical period of weed control in white bean starts at the appearance of the second trifoliate and lasts from 3 to 5 wk thereafter (Woolley et al 1993). The results presented here suggest that weed management in snap bean should not be delayed until the appearance of the second trifoliate.…”
Section: Resultsmentioning
confidence: 71%
“…Total yield, expressed as a percentage of the weed-free control as a function of time, was examined by non-linear leastsquares regression using PROC NLIN (SAS, 1996). Gompertz and logistic equations were fitted to the yield data for increasing duration of weed-free and weed-infested periods respectively (Van Acker et al, 1993;Woolley et al, 1993). The Gompertz model used consisted of three parameters:…”
Section: Discussionmentioning
confidence: 99%
“…Ghosheh et al (1996) pointed out that long critical periods are indicative of more competitive weeds or less competitive crops (Oliver, 1988). Woolley et al (1993) found that the critical period of weed control might vary depending upon crop cultivars and weed pressure levels among other factors.…”
Section: Critical Period Of Weed Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergence is a crucial event in the life cycle of annual plants (Forcella et al 2000); plants transition to autotrophic growth during emergence, and differences in emergence timing can alter their competitiveness. Seedlings emerging earlier may sooner depend on exogenous N availability and be more competitive than those emerging later (Hall et al 1992;Knezevic et al 1994Knezevic et al , 1997Mickelson and Harvey 1999;Weaver et al 1992;Woolley et al 1993). Thus, N response should be greater with earlier, rather than later, emergence.…”
mentioning
confidence: 99%